FINANCING AS A KEY FACTOR OF SUSTAINABLE RURAL TOURISM DEVELOPMENT IN THE REPUBLIC OF SERBIA - Radović, Gordana; Košić, Kristina; Demirović, Dunja (Economics of Agriculture, 2018)
The important reason for the lack of rural tourism development, in most rural areas in Serbia, is undefned strategic development directions and the lack of financial investment. The aim of this paper is to highlight the need for the adoption of the strategy for sustainable development of rural tourism in the actual transition period in the Republic of Serbia, with clearly defned development priorities and modalities of fnancing for all segments of rural tourism offer. The adoption of this strategy is necessary in the Republic of Serbia, in the actual transition period, in order to develop rural areas, to reduce regional differences in economic development, and in order to stop actual depopulation process of rural areas. Defning innovative and additional sources of funding is necessary, because the existing are limited and insuffcient. The paper used a method of analysis and synthesis, descriptive, and comparative method.